Terapi Bedah Frenektomi Pada Ankyloglossia: Laporan Kasus - Steffi Triany Arnov; Risyandi Anwar (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Frenectomy is a surgical procedure to remove or eliminate the frenulum, either the labial, buccal, or lingual frenulum. An abnormality of the thickened and tight lingual frenulum of the tongue that results in limitation of tongue movement is called ankyloglossia. This limitation can causes speech problems. A 25-year-old woman with tongue problems, immobility and difficulty in pronouncing certain letters. The tongue cannot cross the vermilion lip line. The choice of surgical treatment is frenectomy under local anesthesia using the dual hemostat method. Frenectomy as a treatment option for ankyloglossia gave good results without complications and was continued with speech therapy rehabilitation.